2016
DOI: 10.1002/mnfr.201500937
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vitamin D levels in type 1 and type 2 diabetes patients: Results from metaanalysis

Abstract: Available data indicated that both T1D and T2D patients had lower levels of 25(OH)D than controls overall. The mechanistic underpinnings of this association warrant further elucidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 57 publications
1
29
0
2
Order By: Relevance
“…The overall recognized immunomodulatory effect of vitamin D has been followed by a large number of studies that have investigated the correlation of vitamin D with immune‐related diseases. In humans, an increased incidence of autoimmune diseases has been reported in subjects with low serum 25OHD in comparison to healthy controls [67‐69]. A higher disease activity has also been reported in patients affected by autoimmune diseases with vitamin D deficiency [70‐72].…”
Section: Discussionmentioning
confidence: 99%
“…The overall recognized immunomodulatory effect of vitamin D has been followed by a large number of studies that have investigated the correlation of vitamin D with immune‐related diseases. In humans, an increased incidence of autoimmune diseases has been reported in subjects with low serum 25OHD in comparison to healthy controls [67‐69]. A higher disease activity has also been reported in patients affected by autoimmune diseases with vitamin D deficiency [70‐72].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it might be more useful to analyze the correlation between the serum 25(OH)D 3 level and autoimmunity. Indeed, in many autoimmune diseases, patients have a lower serum 25(OH)D 3 than healthy controls (3036). In addition, patients with a lower 25(OH)D 3 level are implicated to have higher disease activity (32, 35, 37).…”
Section: Vitamin D and Autoimmune Diseasesmentioning
confidence: 99%
“…In a study conducted in Sweden by Littorin et al, 459 newly diagnosed diabetic patients aged between 15 and 34 years were found to have lower levels of vitamin D than 208 healthy control subjects similar as to age and area of residence, and it was suggested that vitamin D may play a role in the development of type 1 diabetes (11). In the meta-analyzes of Shen et al, involving 2,003 subjects with type 1 DM and 1,882 control patients, 25 (OH) D vitamin levels in patients with type 1 diabetes were found to be lower than in the control group (12).…”
Section: Discussionmentioning
confidence: 94%